Intertemporal choice and income regularity: Non-fungibility in a lab-in-the-field experiment - Kramer, Berber; Kunst, David (International Food Policy Research Institute, 2017)
Motivated by evidence of mental accounting, this paper tests whether the choice of when to be paid depends on the income type. A lab-in-the-field experiment in Kenya asked dairy cooperative members to allocate both their regular milk payments and an irregular windfall between two dates. We find that participants allocated milk payments to the later of the two dates but allocated the windfall to the earlier date. Most participants self-reported deferring their milk payments in order to save for lump-sum expenses. Those planning to use milk payments for smaller, more frequent purchases were less likely to defer payments. Farmers hence appeared to earmark regular milk payments, but not the irregular windfall, for bulky expenditures. This behavior potentially explains why discount rates elicited using experimenter money are often higher than those inferred from observed choices over regular income. Given that compliance with informal contracts depends on whether the timing of payments aligns with recipient preferences, these findings also have implications for contract design in rural value chains.